Multiple Adaptive Strategies of Himalayan Iodobacter sp. PCH194 to High-Altitude Stresses - Kumar, Vijay; Kashyap, Prakriti; Kumar, Subhash; Thakur, Vikas; Kumar, Sanjay; Singh, Dharam (Frontiers in Microbiology, 2022)
Bacterial adaption to the multiple stressed environments of high-altitude niches in the Himalayas is intriguing and is of considerable interest to biotechnologists. Previously, we performed culturable and unculturable metagenome microbial diversity from glacial and kettle lakes in the Western Himalayas. Here, we explored the adaptive strategies of a unique Himalayan eurypsychrophile Iodobacter sp. PCH194, which can synthesize polyhydroxybutyrate (PHB) and violacein pigment. Whole-genome sequencing and analysis of Iodobacter sp. PCH194 (4.58 Mb chromosome and three plasmids) revealed genetic traits associated with adaptive strategies for cold/freeze, nutritional fluctuation, defence against UV, acidic pH, and the kettle lake's competitive environment. Differential proteome analysis suggested the adaptive role of chaperones, ribonucleases, secretion system, and antifreeze proteins under cold stress. Antifreeze activity inhibiting the ice recrystallization at -9℃ demonstrated the bacterium's survival at subzero temperature. The bacterium stores carbon in the form of PHB under stress conditions responding to nutritional fluctuations. However, violacein pigment protects the cells from UV radiation. Concisely, genomic, proteomic, and physiological studies revealed the multiple adaptive strategies of Himalayan Iodobacter to survive in the high-altitude kettle lake.